Answer:
3
Step-by-step explanation:
3/4 divided by 1/4 equals 3
Answer: The required solution is
![y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cdfrac%7B7%7D%7B3%7De%5E%7B-t%7D%2B%5Cdfrac%7B7%7D%7B3%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Step-by-step explanation: We are given to solve the following differential equation :
![5y^{\prime\prime}+3y^\prime-2y=0,~~~~~~~y(0)=0,~~y^\prime(0)=2.8~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://tex.z-dn.net/?f=5y%5E%7B%5Cprime%5Cprime%7D%2B3y%5E%5Cprime-2y%3D0%2C~~~~~~~y%280%29%3D0%2C~~y%5E%5Cprime%280%29%3D2.8~~~~~~~~~~~~~~~~~~~~~~~~%28i%29)
Let us consider that
be an auxiliary solution of equation (i).
Then, we have
![y^prime=me^{mt},~~~~~y^{\prime\prime}=m^2e^{mt}.](https://tex.z-dn.net/?f=y%5Eprime%3Dme%5E%7Bmt%7D%2C~~~~~y%5E%7B%5Cprime%5Cprime%7D%3Dm%5E2e%5E%7Bmt%7D.)
Substituting these values in equation (i), we get
![5m^2e^{mt}+3me^{mt}-2e^{mt}=0\\\\\Rightarrow (5m^2+3y-2)e^{mt}=0\\\\\Rightarrow 5m^2+3m-2=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^{mt}\neq0]\\\\\Rightarrow 5m^2+5m-2m-2=0\\\\\Rightarrow 5m(m+1)-2(m+1)=0\\\\\Rightarrow (m+1)(5m-1)=0\\\\\Rightarrow m+1=0,~~~~~5m-1=0\\\\\Rightarrow m=-1,~\dfrac{1}{5}.](https://tex.z-dn.net/?f=5m%5E2e%5E%7Bmt%7D%2B3me%5E%7Bmt%7D-2e%5E%7Bmt%7D%3D0%5C%5C%5C%5C%5CRightarrow%20%285m%5E2%2B3y-2%29e%5E%7Bmt%7D%3D0%5C%5C%5C%5C%5CRightarrow%205m%5E2%2B3m-2%3D0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%5B%5Ctextup%7Bsince%20%7De%5E%7Bmt%7D%5Cneq0%5D%5C%5C%5C%5C%5CRightarrow%205m%5E2%2B5m-2m-2%3D0%5C%5C%5C%5C%5CRightarrow%205m%28m%2B1%29-2%28m%2B1%29%3D0%5C%5C%5C%5C%5CRightarrow%20%28m%2B1%29%285m-1%29%3D0%5C%5C%5C%5C%5CRightarrow%20m%2B1%3D0%2C~~~~~5m-1%3D0%5C%5C%5C%5C%5CRightarrow%20m%3D-1%2C~%5Cdfrac%7B1%7D%7B5%7D.)
So, the general solution of the given equation is
![y(t)=Ae^{-t}+Be^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3DAe%5E%7B-t%7D%2BBe%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Differentiating with respect to t, we get
![y^\prime(t)=-Ae^{-t}+\dfrac{B}{5}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%5E%5Cprime%28t%29%3D-Ae%5E%7B-t%7D%2B%5Cdfrac%7BB%7D%7B5%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
According to the given conditions, we have
![y(0)=0\\\\\Rightarrow A+B=0\\\\\Rightarrow B=-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=y%280%29%3D0%5C%5C%5C%5C%5CRightarrow%20A%2BB%3D0%5C%5C%5C%5C%5CRightarrow%20B%3D-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
and
![y^\prime(0)=2.8\\\\\Rightarrow -A+\dfrac{B}{5}=2.8\\\\\Rightarrow -5A+B=14\\\\\Rightarrow -5A-A=14~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{Uisng equation (ii)}]\\\\\Rightarrow -6A=14\\\\\Rightarrow A=-\dfrac{14}{6}\\\\\Rightarrow A=-\dfrac{7}{3}.](https://tex.z-dn.net/?f=y%5E%5Cprime%280%29%3D2.8%5C%5C%5C%5C%5CRightarrow%20-A%2B%5Cdfrac%7BB%7D%7B5%7D%3D2.8%5C%5C%5C%5C%5CRightarrow%20-5A%2BB%3D14%5C%5C%5C%5C%5CRightarrow%20-5A-A%3D14~~~~~~~~~~~~~~~~~~~~~~~~~~~%5B%5Ctextup%7BUisng%20equation%20%28ii%29%7D%5D%5C%5C%5C%5C%5CRightarrow%20-6A%3D14%5C%5C%5C%5C%5CRightarrow%20A%3D-%5Cdfrac%7B14%7D%7B6%7D%5C%5C%5C%5C%5CRightarrow%20A%3D-%5Cdfrac%7B7%7D%7B3%7D.)
From equation (ii), we get
![B=\dfrac{7}{3}.](https://tex.z-dn.net/?f=B%3D%5Cdfrac%7B7%7D%7B3%7D.)
Thus, the required solution is
![y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cdfrac%7B7%7D%7B3%7De%5E%7B-t%7D%2B%5Cdfrac%7B7%7D%7B3%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Answer:
B. Y=2/5x+2
Explanation:
Y-intercept: (0,2)
Slope: 4-2. 2
——=
5-0. 5
Y=2/5+2
Answer:
7
Step-by-step explanation:
Property of addition:
-2 = 2x - 16
again
14 = 2x
property of division
7 = x
x = 7